The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/plants11060814
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Addition Alters C: N: P Stoichiometry in Moss Crust-Soil Continuum in Gurbantünggüt Desert

Abstract: The biogeochemical cycling of soil elements in ecosystems has changed under global changes, including nutrients essential for plant growth. The application of biochar can improve the utilization of soil nutrients by plants and change the stoichiometry of carbon (C), nitrogen (N), and phosphorus (P) in plants and soil. However, the response of ecological stoichiometry in a moss crust-soil continuum to local plant biochar addition in a desert ecosystem has not been comprehensively explored. Here, we conducted a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Many studies have shown that biochar application improves soil total nutrient contents [49,50]. This study indicated that biochar additions were beneficial to soil nutrients of total C, total P and total K (Figure 3), and increased the soil's available nutrient contents (Figure 4).…”
Section: Effects Of Biochar Addition On Soil Propertymentioning
confidence: 68%
“…Many studies have shown that biochar application improves soil total nutrient contents [49,50]. This study indicated that biochar additions were beneficial to soil nutrients of total C, total P and total K (Figure 3), and increased the soil's available nutrient contents (Figure 4).…”
Section: Effects Of Biochar Addition On Soil Propertymentioning
confidence: 68%
“…Several factors could explain this observation. (1): Biochar contains rich pore structures, which can reduce the rate of soil nutrient release and reduce nutrient loss [ 40 ]. (2): Biochar has a higher charge density, which can effectively absorb soil nutrients and improve nutrient utilization [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors could explain this observation. (1): Biochar contains rich pore structures, which can reduce the rate of soil nutrient release and reduce nutrient loss [40].…”
Section: Effects Of Biochar and Straw On The Soil Chemical Properties...mentioning
confidence: 99%
“…Therefore, it is urgent for humans to face up to the study of plant species diversity in the desert [19]. Desert ecosystems are more barren than other ecosystems, and plant growth is limited by environmental factors such as soil nutrients [20]. The limited and uneven distribution of water and nutrients leads to plants appearing in strips or patches [21].…”
Section: Introductionmentioning
confidence: 99%